Memaknai Perolehan Rezki dalam Hukum Ekonomi Syariah - Yenti, Endri; Hasramita, Hasramita; Alwana, Hanif Aidhil (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Islam as a religion that has universal teachings, not only talks about aqidah as the main foundation of people in adhering to religion, but also teaches good relations among humans (muamalah). In Islam, the discussion of economics cannot be separated from the concept of sustenance, some people assume that sustenance is identical to property, because economic activity is an activity to fulfill material needs or property (al-Mal) as a life support. Economic activity is an effort to fulfill basic human needs in order to worship Allah SWT. Therefore, it must be ensured through the rules and methods justified by sharia. Although in principle various types of muamalah are permitted, the concept of usury is strictly not justified in sharia economic law, so it must also be ensured that in meeting daily needs, Muslims must obey these limits and provisions. The method used in this paper is to reveal the meaning of the limitations (arguments) of the Qur'an and Sunnah regarding the acquisition of sustenance then analyzed based on the sociological ethical aspects of Islamic economic law activities. And in this paper the activities of usury and gharar are one of the enemies of Islamic economics in the perspective of Islamic law.Islam sebagai suatu agama yang memiliki ajaran universal, tidak hanya bicara tentang aqidah sebagai pondasi utama umat dalam menganut agama, tapi juga mengajarkan hubungan baik sesama manusia (muamalah). Dalam Islam, bahasan ekonomi tidak terlepas dari konsep rezki, sebagian masyarakat mengasumsikan bahwa rezki identik dengan harta, karena kegiatan ekonomi merupakan aktifitas pemenuhan kebutuhan material atau harta (al-Mal) sebagai penyangga kehidupan. Aktifitas ekonomi merupakan usaha pemenuhan kebutuhan dasar manusia dalam rangka menjalankan ibadah kepada Allah SWT. Oleh karenanya mesti dipastikan melalui aturan dan cara yang dibenarkan syariah. Sekalipun pada prinsipnya, berbagai jenis muamalah dibolehkan. Konsep riba dengan tegas tidak dibenarkan dalam hukum ekonomi syariah, maka harus dipastikan pula dalam pemenuhan kebutuhan sehari-hari, umat Islam harus patuh pada batas dan ketentuan tersebut. Metode yang digunakan dalam tulisan ini ialah dengan mengungkap makna batasan (dalil) dari al-Qur`an dan Sunnah tentang perolehan rezki, kemudian dianalisis berdasarkan aspek etik sosiologis aktifitas hukum ekonomi Syariah. Dan dalam tulisan ini, aktifitas riba dan gharar menjadi salah satu musuh ekonomi dalam persepktif ekonomi syariah.